2021
DOI: 10.1016/j.pcd.2021.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID-19 pandemic on self-management in patients with type 2 diabetics

Abstract: Aims: The research was conducted with the aim of determining the effect of the COVID-19 pandemic on levels of self-management in individuals with type 2 diabetes. Methods: This cross-sectional descriptive type of study was conducted between 21 December 2020 and 1 April 2021. It was performed with 378 individuals with type 2 diabetes attending the endocrinology clinic and outpatients' department of a government hospital who agreed to participate in the research. In the collection of data, a Patient Identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 24 publications
10
41
1
Order By: Relevance
“…Three studies examined global diabetes self-care scores. One study reported no change (37) and two studies (59,60) reported decreased total diabetes self-care scores. Silva-Tinoco et al (59) found that higher pre-pandemic self-care was related to fewer problems with self-care during the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies examined global diabetes self-care scores. One study reported no change (37) and two studies (59,60) reported decreased total diabetes self-care scores. Silva-Tinoco et al (59) found that higher pre-pandemic self-care was related to fewer problems with self-care during the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Cheng et al (33) reported increased sleep and Hasegawa et al (38) reported increased sleep duration. One study reported decreased sleep quality (60). Four studies reported that the modal response was no changes in sleep (35,45,48,58).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this study was performed during the very early phase of the COVID-19 pandemic in Romania, it emphasises the importance of optimal management of DM to avoid uncontrolled hyperglycaemia and future complications [ 34 ]. The COVID-19 pandemic has had a major impact on Romanian society [ 35 ]; this has important implications for patients with DM, because the DSMQ was negatively influenced by the pandemic in other studies [ 36 ]. Patients with DM are among the most vulnerable to severity and mortality from COVID-19 [ 37 ] and are experiencing challenges in accessing healthcare facilities and clinic visits; this is contributing to the increase in their cardiometabolic complications [ 38 ].…”
Section: Discussionmentioning
confidence: 99%